1997
DOI: 10.1002/hep.510260110
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the impairment of the glucagon-stimulated phosphoenolpyruvate carboxykinase gene expression by interleukin-6 in rat hepatocytes: Inhibition of the increase in cyclic 3?,5? adenosine monophosphate and the downstream cyclic 3?,5? adenosine monophosphate action

Abstract: ferase reporter gene construct under the control of a PCK In cultured rat hepatocytes, the gluconeogenic key enzyme, phosphoenolpyruvate carboxykinase (PCK), is induced by gene promoter fragment (base 0979 to base /32). Luciferase activity was determined after stimulation of the cells with glucagon via elevation of cyclic 3 ,5 adenosine monophosphate (cAMP). The proinflammatory cytokine, interleukin-6 CPT-cAMP in the absence or presence of IL-6. CPT-cAMP increased luciferase activity by 1.7-fold, which was inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
5

Year Published

2000
2000
2008
2008

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 6 publications
(6 reference statements)
2
6
0
5
Order By: Relevance
“…Insulin, the physiological antagonist of glucagon action, decreases the glucagon-stimulated increase in cAMP by the activation of phosphodiesterase, thereby attenuating the stimulation by glucagon of PCK gene expression [14,15,22]. In the present study insulin inhibited the stimulation by glucagon or cAMP of luciferase expression from the human as well as from the rat cytosolic PCK gene promoter, indicating that insulin was antagonistic through both promoters.…”
Section: Stimulation By Glucagon (Camp) Of the Human And Rat Pck Genesupporting
confidence: 51%
See 2 more Smart Citations
“…Insulin, the physiological antagonist of glucagon action, decreases the glucagon-stimulated increase in cAMP by the activation of phosphodiesterase, thereby attenuating the stimulation by glucagon of PCK gene expression [14,15,22]. In the present study insulin inhibited the stimulation by glucagon or cAMP of luciferase expression from the human as well as from the rat cytosolic PCK gene promoter, indicating that insulin was antagonistic through both promoters.…”
Section: Stimulation By Glucagon (Camp) Of the Human And Rat Pck Genesupporting
confidence: 51%
“…In the present study insulin inhibited the stimulation by glucagon or cAMP of luciferase expression from the human as well as from the rat cytosolic PCK gene promoter, indicating that insulin was antagonistic through both promoters. However, because insulin is also inhibitory when the non-hydrolysable cAMP analogue CPT-cAMP is used, the effect must occur downstream from cAMP hydrolysis, as has been suggested previously [22,25].…”
Section: Stimulation By Glucagon (Camp) Of the Human And Rat Pck Genementioning
confidence: 89%
See 1 more Smart Citation
“…Hence, at high cAMP concentrations the inhibitory effect of the cytokines on the increase in PCK1 mRNA could be overridden ( Table 1 ). Under the same conditions, it has been shown that the inhibition by insulin of the glucagon-stimulated increase in cAMP levels could be prevented in the presence of IBMX [9] . This was expected, because insulin is known to counteract the increase in cAMP by the activation of phosphodiesterase [14] .…”
Section: Mechanism Of the Attenuation By Rhil1 And Rhtnf Of The Incrementioning
confidence: 90%
“…PCK1 mRNA and cAMP levels were determined after 2 hours, and 3 minutes, respectively, at which points in time, levels were increased transiently to a maximum after glucagon addition as shown in previous studies. This increase in mRNA and cAMP at 2 hours, and 3 minutes, respectively, after glucagon addition, was set equal to 100 % in each single experiment, relative to other values [9,10] . Under these conditions, the cytokines still inhibited the glucagon-stimulated increase in cAMP and in PCK1 mRNA indicating that this inhibition was not mediated by the activation of an inhibitory G-protein ( Table 1 ).…”
Section: Mechanism Of the Attenuation By Rhil1 And Rhtnf Of The Incrementioning
confidence: 99%